Model Plea Bargaining pada Sistem Penuntutan Indonesia dalam Perspektif Jaksa - Gunowo, Salis (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study explores the feasibility of adopting plea bargaining within the Indonesian criminal prosecution system from the perspective of public prosecutors. Unlike common law jurisdictions such as the United States and Canada, where plea bargaining has become the dominant mechanism for resolving criminal cases, Indonesia still relies on full trials, resulting in significant case backlogs and overcapacity in correctional institutions. Employing a socio-legal qualitative approach, this research collected data through in-depth interviews with 25 prosecutors from three different jurisdictions, complemented by document analysis and limited observations. The findings reveal that while 72% of prosecutors support the potential adoption of plea bargaining—either entirely or with conditions—28% express rejection due to concerns over legal certainty, possible abuse of power, and the erosion of defendants’ rights to a fair trial. Comparative analysis indicates that prosecutors in urban jurisdictions tend to adopt a more pragmatic stance due to heavy caseloads. At the same time, those in regions dominated by narcotics cases exhibit more conservative views. The study proposes a contextual adaptation model for Indonesia that balances efficiency with substantive justice by involving judicial oversight in the negotiation process. This research contributes academically by providing empirical insights into prosecutors’ perceptions, which are rarely discussed in the Indonesian literature, and, practically, by offering policy recommendations to reform the criminal justice system. The conclusion emphasizes that adopting plea bargaining in Indonesia is feasible, provided it is accompanied by strict regulations, transparent oversight mechanisms, and apparent limitations on its application.